Generating Self-Invertible Matrices by Hill Cipher Algorithm In Gaussian Integers - Ayat A. Jafaar; Rifaat Z. Khalaf (Academic Science Journal)
In this paper, the Creating self-reflexive matrices for the Hill Cipher algorithm in Gaussian integers is discussed. It's not always possible to find the inverse of the matrix that was used to encrypt the plaintext. Therefore, the encrypted text cannot be deciphered if the matrix is not invertible. The encryption matrix utilized in the self-reflexive matrix Creating method is self-reflexive as well. As a result, we do not need to find the matrix's inverse during decryption. Additionally, this approach does away with the computational cost of determining the matrix's inverse during decryption. We also provided an example showing the work of Hill-Cipher using a self-reflecting matrix in Gaussian integers